Impact of Plasma Exposure of Statins and Their Metabolites With Major Adverse Cardiovascular Events in Chinese Patients With Coronary Artery Disease - Zhou, Xiao-hong; Cai, Li-yun; Lai, Wei-Hua; Bai, Xue; Liu, Yi-bin; Zhu, Qian; He, Guo-dong; Chen, Ji-Yan; Huang, Min; Zhou, Zhi-ling; Zhong, Shi-long (Frontiers in Pharmacology, 2020)
The selection of optimum statin intensity is inconclusive, and the association of the plasma exposure of statins and metabolites with major adverse cardiovascular events (MACE) is unclear. This study sought to compare the effect of low(quartile 1), intermediate (quartile 2 and 3), and high(quartile 4) plasma exposure of statins and metabolites on MACE, re-ischemia events and death in patients with coronary artery disease (CAD) at 5 years. A total of 1644 patients in atorvastatin (AT) cohort and 804 patients in rosuvastatin (RST) cohort were included, and their plasma concentration of statins and metabolites was categorized as low-, mid-, or high-group. The association between the plasma levels of statins and metabolites and the incidence of primary endpoint in patients was assessed by Cox proportional hazard models. Intensive AT exposure (Q4 > 5.32 ng/mL) was significantly associated with increased risk of death compared with low (hazard ratio [HR]: 1.522; 95% confidence interval [CI]: 1.035–1.061; P = 0.0022) or moderate exposure (HR: 2.054; 95% CI: 1.348–3.130; P = 0.0008). This association was also found in AT’s five metabolites (all P < 0.01). In patients with RST treatment, moderate RST concentration (0.53–4.29 ng/mL) versus low concentration had a significantly lower risk of MACE and re-ischemia events. (HR: 0.532, 95% CI: 0.347–0.815, P = 0.0061 and HR: 0.505, 95% CI: 0.310–0.823, P = 0.0061, respectively). A higher plasma exposure of AT and metabolites has a significantly higher risk of death, and moderate RST exposure has a significantly lower risk of MACE and re-ischemia events in Chinese patients with CAD. The harms of high plasma exposure should be considered when prescribing statins to patients because it may be a risk factor for having poor prognosis in patients with CAD.